Factors Affecting Intention to Stay Among Nursing Staff at Selected Private Hospitals - Nur Adnin Ariffin; Yee Bit-Lian (Caring: Indonesian Journal of Nursing Science, 2022)
Many factors in the healthcare industry affect the nurse's work, but some major factors influence them to leave the organisation. Nurse retention is one of the major challenges faced by the healthcare industry, due to which the turnover rate of nurses increases. The healthcare industry is growing daily and needs more nurses, but due to the exhausting labour and challenging work, most people leave the industry early and look for better opportunities. This study aimed to determine the factors affecting nursing retention and turnover in a selected private hospital in Selangor, Malaysia. This descriptive, cross-sectional quantitative study involved 133 nursing staff through a self-administered survey questionnaire to know the respondents' viewpoints; the participants gave mixed responses about staying and leaving the organisation. However, from their statements, it is clear that they wanted the industry to improve the training and development process, work-life balance and reward and recognition policy. The high turnover rate of nurses will cause detrimental effects on patient care if nurses' lack of training and development influence nurses to leave the organisation. Â